A Influência das redes sociais na avaliação da sustentabilidade das competências essenciais em uma organização pública - Teixeira, Dayseanne Costa (2017)
Since it is recognized the importance of the middle managers for the execution of the organizations strategy and that social networks have a strong impact in the information sharing and formation of opinions of the involved subjects, this study had as objective to investigate the influence of the social networks structures of the intermediary managers in their perception about the performance and sustainability of the core competences of the organization. For this, we chose the case study as a research strategy, and Universidade Federal de Alagoas - UFAL as the case. Various methods of data collection were used, including interviews, documentary analysis and survey application. The data were analyzed in the light of the Social Networks Analysis - SNA, resulting in a description of the middle managers network structure. All types of relationships evaluated indicated decentralized and sparse networks, almost always repeating the same central actors. Regarding the evaluation of the competences, all were identified with a moderate performance, a high level of tacitness and moderate / high level of robustness and embeddedness. However, the level of consensus among managers was low. Considering these results, a plan of action was elaborated, understanding that the most important interventions should promote greater interaction within the network, contributing to the dispersion of knowledge and to the embeddedness of competences and the formalization of the tacit knowledge dispersed in the organization. The relationship between social networks and competences is a topic that deserves further study, and therefore, for future research, it is proposed to extend and replicate this study in organizations with different characteristics.